EFFECT OF PROPELLER DESIGN ON PROPELLER EFFICIENCY ON CARGO SHIPS - Kusuma, Cahya; Indiaryanto, Mahendra (Department of Marine Engineering, Universitas Hang Tuah, 2025)
This research examines the effect of the use of propellers on propeller performance on cargo ships. Using computational fluid analysis (CFD), the study evaluated the fluid flow around the propeller under two conditions: with and without a propeller. Shows an increase in propeller efficiency of up to 15% at cruising speed with the use of propellers. The implication of these results is the potential application of propeller technology to improve the overall efficiency and performance of cargo ships. Through a combined approach of numerical simulation and experimental testing, we conducted an in-depth analysis of various propeller designs. With factors such as shape, size, angle of attack, and propeller profile in evaluating propeller performance. Empirical data were obtained through trials at a model ship test facility and compared with computer simulation results. The results of this study provide valuable insights for the shipping industry in improving the operational efficiency of cargo ships. These findings can be used by shipping companies and shipbuilders to optimize propeller designs and improve their operational efficiency.